Analisis Kondisi Pemukiman Penduduk Kabupaten/Kota di Indonesia - Sri Nathasya; TRI HARYANTO; Ni Made Sukartini (Jurusan Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis, Universitas Lampung, 2020)
The settlement is a very important topic and is widely discussed in all countries. This study is a study that discusses the topic of settlement using the literature review method. In this study, we will discuss several articles related to housing and try to compare with the conditions of settlements in Indonesia. The findings of this study are that there are two aspects of empirical research that are not found to be running optimally in Indonesia, namely: aspects of consumption patterns and urban and environmental planning. Meanwhile, the empirical condition that is under the conditions of housing in Indonesia is the limited quality of human resources and types of housing in Indonesia as well as aspects of the interaction between the public sector, the interaction of the private sector to increase settlement growth.